Guilty plea hearings and judicial supervision: Some differences between federal and state judges regarding Rule 11 and a defendant’s right to due process - Champion, Dean J. (American journal of criminal justice, 1987)
Samples of 120 district court judges from six randomly selected circuit court jurisdictions were compared with 62 circuit and criminal court judges in Tennessee concerning their compliance with Rule 11 of the Federal Rules of Criminal Procedure (U.S.C.A., 1986) governing guilty plea hearings. Among other things, Rule 11 provides that judges will inquire of defendants in open court about the voluntariness of their guilty pleas, whether they understand that they are waiving several important constitutional rights, whether there is a factual basis for the guilty plea, whether they realize they have a right to an attorney, and whether they understand the nature and consequences of the charges against them. It was found that federal judges are substantially in compliance with these provisions of Rule 11, although full compliance was not observed for all issue areas. By comparison, Tennessee trial judges adhered to these provisions (duplicated in the Tennessee Rules of Criminal Procedure verbatim) much less frequently. Various reasons for these discrepancies are discussed, as are some implications for defendant’s access to due process and certain constitutional guarantees.